IN VITRO GERMINATION OF ANTI-DIABETIC PLANT LOQUAT (Eriobotrya japonica Lindl.) TO PRODUCE GOOD SEEDLING - ISNAINI NURWAHYUNI; HENDA NAULI MARPAUNG; SUCI RAHAYU (International Journal of Pharma and Bio Sciences, 2017)
The aim of the study is to obtain good seedling of anti-diabetic plant Loquat (Eriobotrya japonica Lindl.) through in vitro germination by using growth stimulator of gibberellic acid (GA3) and kinetin. The study is carried out using a completely randomized design with two factors, the concentrations of GA3 (0, 250 and 500 mg/L) and the kinetin (0, 4, 8 and 12 mg/L). The results showed that the technique has successfully shortened the germination time of loquat seed and stimulate the growth development of shoots, leaves and roots. The GA3 and kinetin at optimum condition are found very effective to stimulate seed germination and growth of loquat seedlings. Combination of 500 mg/L GA3 and 8 mg/L kinetin, followed by 250 mg/L GA3 and 4 mg/L kinetin was observed to be the best experimental condition to produce good quality seedling. It was also observed that high concentration of 500 mg/L GA3 alone is very effective to improve the growth of loquat root. The study is promising to obtain good seedling of loquat plants.